2014
DOI: 10.1128/aac.02506-14
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Dissemination of CTX-M-5-Producing Hypermutable Salmonella enterica Serovar Typhimurium Sequence Type 328 Strains in Russia, Belarus, and Kazakhstan

Abstract: e In this paper, we present evidence of long-term circulation of cefotaxime-resistant clonally related Salmonella enterica serovar Typhimurium strains over a broad geographic area. The genetic relatedness of 88 isolates collected from multiple outbreaks and sporadic cases of nosocomial salmonellosis in various parts of Russia, Belarus, and Kazakhstan from 1996 to 2009 was established by multilocus tandem-repeat analysis (MLVA) and multilocus sequence typing (MLST). The isolates belong to sequence type 328 (ST3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 57 publications
3
13
0
Order By: Relevance
“…This latter sequence type of Salmonella Typhimurium was recovered in Japan, Taiwan, Russia, United Kingdom and Scotland (25). As reported by Kozyreva et al, this strain was probably lacking the pSLT virulent plasmid of Salmonella Typhimurium (25). Three of the tested loci, STTR5, STTR6 and STTR10, displayed a high degree of polymorphism indicated by 0.611, 0.72, 0.597 indices respectively, which were comparable with previous reports.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This latter sequence type of Salmonella Typhimurium was recovered in Japan, Taiwan, Russia, United Kingdom and Scotland (25). As reported by Kozyreva et al, this strain was probably lacking the pSLT virulent plasmid of Salmonella Typhimurium (25). Three of the tested loci, STTR5, STTR6 and STTR10, displayed a high degree of polymorphism indicated by 0.611, 0.72, 0.597 indices respectively, which were comparable with previous reports.…”
Section: Discussionsupporting
confidence: 90%
“…Four loci were present in all tested isolates, while STTR10pl was absent from one isolate ST328. This latter sequence type of Salmonella Typhimurium was recovered in Japan, Taiwan, Russia, United Kingdom and Scotland . As reported by Kozyreva et al, this strain was probably lacking the pSLT virulent plasmid of Salmonella Typhimurium .…”
Section: Discussionsupporting
confidence: 68%
“…were completely resistant to nalidixic acid and gentamycin during the 2012 and 2013 outbreaks in Iran; these findings are consistent with the data from other studies in Iran and neighboring countries (24)(25)(26). A study by Ashtiani et al (27) out of Iran showed that the resistance rate to nalidixic acid was 42.3%.…”
Section: Discussionsupporting
confidence: 82%
“…Bacterial strains with a mutator phenotype have an elevated mutation rate, typically due to mutations in genes encoding components of DNA replication and repair pathways [49]. Mutator phenotypes are commonly found in clinical bacterial populations and may contribute significantly to the acquisition of antimicrobial resistance [50][51][52]. For example, the mutator phenotype has been attributed to the development of multidrug-resistant S. typhimurium [50].…”
Section: Have We Seen It Before? Impact Of High-resolution Molecular mentioning
confidence: 99%
“…Mutator phenotypes are commonly found in clinical bacterial populations and may contribute significantly to the acquisition of antimicrobial resistance [50][51][52]. For example, the mutator phenotype has been attributed to the development of multidrug-resistant S. typhimurium [50]. In E. coli, this phenotype has recently been shown to be induced in response to stress conditions [53].…”
Section: Have We Seen It Before? Impact Of High-resolution Molecular mentioning
confidence: 99%